The Four Gospels copied by Maximus of Tao in the Jerusalem Collection of Georgian Manuscripts - Kekelia, Vladimer (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
The article examines a manuscript stored in the library of the Orthodox Patriarchate of Jerusalem, providing a description of the manuscript and published the colophons. According to the colophon of the second scribe, the Gospel was written during the reign of Constantin I (1293-1327), son of David VI Narin, the king of western Georgia. Through his efforts, in 1310 the Georgians were regained their main Holy Cross monastery in the Holy Land, which had been captured by the Egyptian Mamluks in 1272. It is likely, in memory of this significant achievement, it can be assumed that on his initiative, this richly illustrated manuscript was rewritten and donated to the Monastery of the Holy Cross in Jerusalem, possibly, under his patronage. Based on this, the manuscript can be dated to the second decade of the 14th century.